Pregnancy-related low back pain in women in Turkey: Prevalence and risk factors - ŞENCAN, SAVAŞ (ELSEVIER MASSON, 2018)
Objectives: To investigate the prevalence of pregnancy-related low back pain (PRLBP) in women in Turkey, identify the factors associated with PRLBP and predict the risk of PRLBP. Materials and methods: This cross-sectional study included a total of 1500 pregnant women admitted to a prenatal care clinic in a secondary care hospital in Turkey between August 2011 and September 2014. All participants were asked to complete a survey questionnaire. The pregnant women who reported recurrent or continuous pain in the lumbar spine or pelvis for more than 1 week were offered a clinical examination for PRLBP by the spine physiatrist. The main outcome measure was the presence of PRLBP. We collected data on sociodemographic factors, previous obstetric history, daily habits, history of LBP, and functional disability scores as assessed by the Oswestry Disability Index (ODI). Results: The mean age of the 1500 women was 26.5 +/- 5.5 years. The prevalence of PRLBP was 53.9%, mostly in the third trimester. Women with PRLBP in the third trimester were more disabled than those in the first and second trimesters (mean ODI 40.0 +/- 16.7 vs. 34.9 +/- 19.2 and 37.4 +/- 15.3, respectively). Risk factors of PRLBP were history of LBP, PRLBP, and menstruation-related LBP as well as no housework assistance (OR = 5.394, 95% CI: 3.128-9.300, P < 0.001; 3.692, 2.745-4.964, P < 0.001; 2.141, 1.563-2.932, P < 0.001; 1.300, 1.029-1.64, P = 0.028, respectively). Conclusion: This cross-sectional study is the largest study of PRLBP in the literature and showed that about 1 in 2 women have PRLBP in any stage of pregnancy. History of LBP related and unrelated to previous pregnancy and menstruation are strong risk factors for PRLBP. Receiving no housework assistance is another risk factor. (C) 2017 Elsevier Masson SAS. All rights reserved.
Keywords: Pregnancy; Low back pain; Prevalance; Risk factors; Disability; PELVIC PAIN; GENERAL-POPULATION; LUMBOPELVIC PAIN; ASSOCIATION; DAMAGE